Green Entrepreneurship and Environmental Sustainability: Current Trends and Future Directions - Safitri, Camelia (Penelitian dan Pengembangan Ilmu, 2024)
This research examines green entrepreneurship as a business strategy that integrates economic value with environmental sustainability principles. Using a systematic literature review method with the PRISMA approach, this research identifies key factors that influence the sustainability of green businesses in developing markets. The research results show that technological innovation, policy support, and green supply chain management are the main factors in the long-term sustainability of green businesses. The implications of this research are important for entrepreneurs and policy makers in developing effective strategies to support green entrepreneurial practices.